Love as a Performative Act in the Stories of Leposava Mijušković (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper analyzes the short stories of Leposava Mijušković. It reveals their place in the context of Serbian literature and analyzes the reception of her work during her life and after her death. The applied narrative methods such as stream of consciousness technique, fragmentarity of text, discontinuous comprehension of time, and subjectivist perspectives and interiorization of storytelling, locate these short stories in the context of early Serbian modernism, which implies a break with the realist narrative. Content analysis of the stories defines love as their thematic framework, and on that basis these stories are included in the discourse of romantic literature. It reveals their belonging to the intimate genres, characteristic for women's literature in the early twentieth century, and recognizes genre affiliation to Foucault’s understanding of confession, which, in addition to romantic themes, includes autobiographical foundation and analytical narratives. The analysis of the main characters shows generative and performative moments of their gender identity.
Keywords: modernism; intimate genre; romantic discourse; confession; melancholy; psychoanalysis